Eastern Indonesia Incorporated Policy Strategy in Eastern Indonesia (Jurnal Bina Praja, 2017)
This study is about the development gap in eastern Indonesia. This research is motivated by the existence of big problems that still faced by Indonesia up to now is the happening of development gap. The purpose of this research is the policy strategy in overcoming the gap between eastern Indonesia and West Indonesia region. This research uses the qualitative approach with discourse analysis method. Data collection method is done by triangulation technique of data source. Meanwhile, the data processing conducted by the researcher is data reduction. The result of this study is to provide an alternative policy that can be used and somewhat different from the mainstream which usually overcomes the gap by directly implementing the infrastructure development policy which until now based on the evaluation did not directly solve the problem, as evidenced by the many results of the construction of the stagnant infrastructure. Through this study, it is found that there are major issues that are more fundamental and often overlooked by policy makers. The main issues are grouped into three major groups of major issues, namely: Comprehensive Planning and Budgeting, Data and Information Effectiveness, and Professionalism of Civil State Apparatus.
Keywords: Development Gaps; Comprehensive Planning; Data Effectiveness; Professionalism of Civil State Apparatus